Sensitivity analysis of observational nudging methodology to reduce error in wind resource assessment (WRA) in the North Sea. (May 2018) - Mylonas, M.P.; Barbouchi, S.; Herrmann, H.; Nastos, P.T.
Abstract: Towards the improvement of the mesoscale modeling for offshore wind application, the real time observational nudging capability of the Weather Research and Forecasting (WRF) model has been implemented aiming for enhanced model performance. Utilizing three different horizontal levels of the offshore meteorological mast, FINO3, in the North Sea, wind speed observations were integrated into the model core. The performance of this modified model was then assessed for three different atmospheric stability conditions. Results from this study, illustrate that for all three stratification cases, there is a significant improvement in model performance when using observational nudging showing a reduction in Root Mean Square Error of up to 27% when compared to the observations from FINO1 platform. This study suggests that observational nudging takes a step towards more accurate simulations in wind resource assessment (WRA). Highlights: WRF model evaluation using observational nudging offshore. Assimilation of wind observations from different vertical levels into WRF. Sensitivity of atmospheric stability. Better results and improvement when using observational nudging. Reducing root mean square error for all atmospheric stability cases.